HUBUNGAN ANTARA MOTIVASI DAN AKTIVITAS BELAJAR SISWA TERHADAP HASIL BELAJAR KOGNITIF SISWA DENGAN PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION PADA KONSEP EKOSISTEM - Nurmahni Harahap (Jurnal Visipena, 2014)
One of the very important process in education is a learning process. The success of the learning process is necessary to motivate the student to be able to encourage their learning activities. STAD cooperative learning is a learning model that trains students to work together in a small group and help each other in solving problems, thus the gain mastery of subject matter understanding. STAD cooperative learning model is not much different from the usual lesson by the teacher. Teachers still contribute in the learning process so that not just released and expected students still easy to adaptable. The purpose of this study was to find out the relationship between motivation and student learning activities with the implementation of STAD. This study used quasi-experimental research method. The population of this study was all first grade students in Model Islamic State Junior High School (MTsN) of Banda Aceh amounting to 39 students chosen from 11 classrooms. Samples were collected by using random sampling technique. Instruments of this study were cognitive learning outcomes test, student motivation questionnaire, and student learning activity observation sheet. Data were analyzed by multiple correlation test at significant level of 0.05. The results of the analysis of research data shows the value of R = 0.56 with P 0.00 (< 0.05) then Ho is rejected and Ha accepted. It can be concluded that there was a significant relationship on student motivation and learning activity toward student cognitive learning outcomes by the implementation of STAD. In order to improve the cognitive learning outcomes,motivation and learning activities optimally it is expected that biology teachers implemented STAD than can actively involve the students in learning process.